Immunotherapy Approaches in Cancer Treatment - Klener, Pavel; Otáhal, Pavel; Lateckova, Lucie; Klener, Pavel (Current pharmaceutical biotechnology, 2015)
Tumor immune surveillance paradigm presumes that most pre-malignant cells or early malignant lesions can be eliminated (or at least controlled) by cells of the immune system. A critical feature that distinguishes advanced tumors from early neoplastic lesions is their capability to evade immune control. As a consequence, vast majority of clinically evident (advanced) tumors are poorly immunogenic. The principle goal of immunotherapy is thus a resurrection of the patient's inefficient or suppressed immune system so that it would once again become capable of launching sustained cytolytic attacks against tumor cells, which would ideally result in total and permanent eradication of cancer. Such activation of patient's anticancer immunity, however, can be achieved by strikingly different ways. This current review discusses diverse innovative immunotherapy approaches, which in the last 20 years achieved miraculous successes in the ever-lasting battle against cancer, including cytokine-based immunotherapy approaches, therapeutic monoclonal antibodies and their derivatives, cancer vaccines, and cell-based immunotherapy approaches.
Keywords: Neoplasms; nádory; Animals; cytokiny; protinádorové vakcíny; Antibodies, Monoclonal; monoklonální protilátky; Cancer Vaccines; lidé; Immunotherapy; zvířata; Cytokines; imunoterapie; antigeny nádorové; Antigens, Neoplasm; Humans